Responding to the Covid-19 pandemic in Zimbabwe: lessons from 2018 cholera outbreak - Simbine, Samuel L.; Muridzo, Noel G.; Chikadzi, Victor; Mafa, Itai (School of Social Work, 2021)
Zimbabwe has been affected by the outbreak of the COVID-19 pandemic like the rest of the world. In the last decade, Zimbabwe has also faced a number of disasters such typhoid, cholera and flooding. In this paper, we argue that Zimbabwe could tap into its past experiences of managing the 2018 cholera outbreak in the fight against the COVID-19 pandemic. The paper draws insights from a qualitative study that sought to understand the challenges and strategies associated with cholera disaster response that happened in 2018. We identify five strategies used by various stakeholders to combat the 2018 cholera outbreak. These strategies include; awareness campaigns, family and contact tracing, coordination meetings, food and non-food items distribution, and setting up treatment and isolation centres. The article juxtaposes the strategies used to combat cholera in 2018 with the World Health Organisation (WHO) recommended COVID-19 strategies and we come to the conclusion that the cholera management strategies could be useful in guiding Zimbabwe's COVID-19 and future pandemics' response strategies.